School students' knowledge and understanding of the Global Solar Ultraviolet Index - Wright, Caradee Yael; Reeder, Anthony I; Albers, Patricia Nicole (South African medical journal, 2015)
The Global Solar Ultraviolet Index (UVI) is a health communication tool used to inform the public about the health risks of excess solar UV radiation and encourage appropriate sun-protection behaviour. Knowledge and understanding of the UVI has been evaluated among adult populations but not among school students. To draw on previously unpublished data from two school-based studies, one in New Zealand (NZ) and the other in South Africa (SA), to investigate and compare students' knowledge of the UVI and, where possible, report their understanding of UVI. Cross-sectional samples of schoolchildren in two countries answered questions on whether they had seen or heard of the UVI and questions aimed at probing their understanding of this measure. Self-report questionnaires were completed by 1 177 students, comprising 472 NZ (264 year 8 (Y8), 214 year 4 (Y4) students) and 705 SA grade 7 primary-school students aged 8-13 years. More than half of the NZ Y8 students answered that they had previously heard about or seen the UVI, whereas significantly more SA students and NZ Y4 students replied that they had neither seen nor heard about the UVI. Among the NZ students who had seen or heard of the UVI, understanding of the tool was fairly good. The observed lack of awareness among many students in both countries provides an opportunity to introduce an innovative and age-appropriate UVI communication method that combines level of risk with behavioural responses to UVI categories and focus on personal relevance to the UVI message.